Risk factors associated with development of dengue haemorrhagic fever or dengue shock syndrome in adults in Hospital Tengku Ampuan Afzan Kuantan - Tee, H. P.; How, Soon Hin; Ab Rahman, Jamalludin; Mohamad Nor, Fariz Safhan; M., Mohd Sapian; Kuan, Yeh Chunn; S., Sapari (Malaysian Medical Associations, 2009)
A retrospective study was conducted to investigate 183 serologically-confirmed cases of dengue fever (DF) admitted from October 2004 to March 2005 in a large hospital in Pahang. Clinical and laboratory features, progress and outcome of these patients were analysed in order to identify risk factors associated with development of dengue haemorrhagic fever (DHF) and dengue shock syndrome (DSS). Individually, we found that older patients, secondary dengue infection, high baseline haematocrit levels, low platelet levels and prolonged activated partial thromboplastin time (APTT) ratio were significant associations with bleeding tendencies. Of these risk factors, haematocrit and APTT ratio were two independent significant risk factors on multivariate analysis. Older patients with primary infection and younger patients with secondary infection had significant bleeding tendencies. We also verified the validity of the haematocrit levels suggested as cut-off levels for plasma leakage for the Malaysian population by Malaysian Clinical Practice Guidelines for Dengue Infection in Adults (2003).